Causal Factor Affected on Self-Care Behavior among Hypertension Patients, Nong Muang Khai Hospital, Phrae Province - โชคทรัพย์สุขกูล สายฝน (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2022)
The purpose of this study was to study the level of self-care behavior and to study the effect of causal factor affected on self-care behavior. The sample consisted of 220 hypertension patients who received the service at Nong Muang Khai Hospital, Phrae Province. The sampling method was systematic random sampling. The questionnaires were used to collect data, confidence coefficient between 0.73-0.97. The data were analyzed by descriptive statistic and multiple regression analysis. The result showed that the people over 15 years old have a moderate level of participation in health activities (= 2.04, SD = 0.80), moderate level of health behavior ( = 3.58, SD = 0.47), and showed that the factor affected health behavior at 0.05 significance level were self-care attitudes (x1), participation in health activities (x2), perceived health, families (x3)’ social support (x4), and perceived benefits (x5) (β = 0.37, 0.36, 0.20, 0.19, and 0.12, respectively). The predictive equation from row score were as follow: Health behavior = 9.71 + 0.20 (x1) + 0.25 (x2) + 0.16 (x3) + 0.42 (x4) + 0.08 (x5)